Potential Health Benefits and Risks Associated with Calisthenics, a Sport of Increasing Popularity – A Literature Review - Wiktor Werenkowicz; Aleksandra Boral; Bartłomiej Czarnecki; Dominika Kryś; Julia Koczur; Michał Górski; Wiktoria Pniok; Wojciech Kurkiewicz; Joanna Brzoza (Journal of Education, Health and Sport)
Introduction and purpose: